Strategi Ekonomi Syariah dalam Mewujudkan Kemakmuran Umat di Indonesia pada Era Modern - Amrin Amrin (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This study aims to examine the strategy of the Islamic economic system in realizing the prosperity of the people in the modern era. This type of research uses a qualitative type with library research. While the research approach used is descriptive analysis. The data analysis used is using qualitative data analysis. The results show that the Islamic economic system in Indonesia has not shown good and significant results in realizing the prosperity of the people. So that it requires steps and strategies in developing sharia economics, namely first, strengthening in increasing public awareness regarding sharia economic literacy, increasing and empowering Human Resources both in quality and quantity, strengthening research and development (R&D) capacity. Second, Strengthening Fatwas, Regulations (Laws) and governance. Third, strengthening and expanding the halal network until the formation of halal in every region throughout Indonesia from upstream to downstream and the halal value chain. Fourth, strengthening the Islamic financial sector Strengthening the Islamic finance sector. Fifth, strengthening micro, medium and macroeconomic enterprises. Sixth, strengthening and developing a digital-based economy.